Antibiotic consumption by New Zealand children: exposure is near universal by the age of 5 years. (13th March 2017) - Hobbs, Mark R.; Grant, Cameron C.; Ritchie, Stephen R.; Chelimo, Carol; Morton, Susan M. B.; Berry, Sarah; Thomas, Mark G.
Abstract : Background: Increasing concerns about antibiotic resistance and microbiome disruption have stimulated interest in describing antibiotic consumption in young children. Young children are an age group for whom antibiotics are frequently prescribed. Objectives: To describe community antibiotic dispensing during the first 5 years of life in a large, socioeconomically and ethnically diverse cohort of children, and to determine how antibiotic dispensing varied between population subgroups. Methods: This study was performed within the Growing Up in New Zealand longitudinal cohort study (www.growingup.co.nz ) with linkage to national administrative antibiotic dispensing data. Descriptive statistics and univariate and multivariable associations were determined. Results: The 5581 cohort children received 53 052 antibiotic courses, of which 54% were amoxicillin. By age 5 years, 97% of children had received one or more antibiotic courses, and each child had received a median of eight antibiotic courses (IQR 4–13). The mean incidence of antibiotic dispensing was 1.9 courses/child/year. Multivariable negative binomial regression showed that Māori and Pacific children received more antibiotic courses than European children, as did children in the most-deprived compared with the least-deprived areas. A distinct seasonal pattern was noted. Conclusions: This study provided a detailed description of antibiotic dispensing within a large and diverse child cohort. Antibiotic exposure was near universal by age 5 years. The predominance of amoxicillin use and the seasonal pattern suggest much antibiotic use may have been for self-limiting respiratory infections. There is a need for safe and effective interventions to improve antibiotic prescribing practices for New Zealand children.